THEORETICAL ISSUES OF INCREASING TEACHING EFFICIENCY BASED ON MODERN ADVANCED PEDAGOGICAL TECHNOLOGIES IN THE PRIMARY CLASS - Abdullayeva Barno Sayfutdinova; Aliyev Nurillo Abdiqayumovich (Galaxy International Interdisciplinary Research Journal, 2022)
How a person grows up in the future depends on the knowledge and upbringing he received in his youth. Good education and high spirituality will deliver a perfect person to the society. In this, the role of the teacher is incomparable. Taking this into account, this article provides information on the theoretical issues of increasing the effectiveness of education based on modern advanced pedagogical technologies in primary school.